2008
DOI: 10.1002/bip.20985
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic contribution to the energy of binding of aromatic ligands with DNA

Abstract: The method of solution of the nonlinear Poisson-Boltzmann equation was used to calculate electrostatic energy of binding of various aromatic ligands with DNA oligomers of different length. Analysis of the electrostatic contribution was made in terms of a two-step DNA binding process: formation of the intercalation cavity and insertion of the ligand. The total electrostatic energy was also partitioned into components: the energy of atom-atom coulombic interactions and the energy of interaction with surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 43 publications
3
34
0
2
Order By: Relevance
“…From this one can make a physically senseless conclusion about that the given physical fac tor does not give a contribution into stabilization of the investigated complexes (see discussion of the problem in work [5]). On the contrary, by a series of authors it has been shown that only the members of decomposi tion not formed by compensation of various interac tions may correlate with charge/structural properties of a ligand and with experimental energy of complex formation (ΔG exp ) [11,12]. Consequently, energetic analysis of the process of complex formation in aque ous medium must operate just with the components of total Gibbs energy on the level of separate physical factors (van der Waals, electrostatic etc.…”
Section: Generalization Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this one can make a physically senseless conclusion about that the given physical fac tor does not give a contribution into stabilization of the investigated complexes (see discussion of the problem in work [5]). On the contrary, by a series of authors it has been shown that only the members of decomposi tion not formed by compensation of various interac tions may correlate with charge/structural properties of a ligand and with experimental energy of complex formation (ΔG exp ) [11,12]. Consequently, energetic analysis of the process of complex formation in aque ous medium must operate just with the components of total Gibbs energy on the level of separate physical factors (van der Waals, electrostatic etc.…”
Section: Generalization Of Resultsmentioning
confidence: 99%
“…The cause of this is dual. Firstly, in a majority of cases the total energies do not demonstrate any correlation with the properties of the very ligand (for example, with charge and type/ramification of side groups [12]) and are there fore useless for interpretation of binding energetics and also during solving problems of QSAR type (directed modification of ligand with an aim of opti mization of its medicobiological effect). Secondly, in consequence of the compensational effect the value of total energy of each separately taken physical factor may be close to zero (for example, ΔG VDW ≈ 0 for inter calators [5] and ΔG EL ≈ 0 for DNA minor groove bind…”
Section: Generalization Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the 10-mer oligonucleotide duplex, d(CGCTCGAGCG) 2 , was used as the model DNA receptor. It was shown that such length of DNA is long enough for correct reproducing of electrostatic interaction for the group of aromatic intercalators [122].…”
Section: Structure Of the Dna Receptormentioning
confidence: 99%
“…The corresponding values of el qualitatively agree with the values Δ im el > 0 quoted in Table 1. At the same time, an increase of the charge density at the center of a complex near two negative poles of dimers results in an energy-favorable interaction with the aqueous environment, Δ solv el < 0, owing to the polarization of the latter (Table 1); this effect is well-known for the binding of charged molecules-intercalators with DNA [35].…”
Section: General Energy Analysis Of Dimerizationmentioning
confidence: 99%